2019
DOI: 10.1186/s12964-019-0366-y
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin protects LPS-induced acute lung injury by modulating Nrf2-mediated oxidative stress and Nrf2-independent NLRP3 and NF-κB pathways

Abstract: Background Oxidative stress and the resulting inflammation are essential pathological processes in acute lung injury (ALI). Nuclear factor erythroid 2-related factor 2 (Nrf2), a vital transcriptional factor, possesses antioxidative potential and has become a primary target to treat many diseases. Oridonin (Ori), isolated from the plant Rabdosia Rrubescens, is a natural substance that possesses antioxidative and anti-inflammatory effects. Our aim was to study whether the anti-inflammatory and antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
133
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(140 citation statements)
references
References 37 publications
7
133
0
Order By: Relevance
“…Among these factors which can induce HO-1 expression, Nrf2 has a key role in regulating cellular antioxidant stress and eliminating reactive oxygen species (ROS) [11]. Recently research found that Nrf2 prevents oxidative stress-induced pulmonary diseases [12,13]. However, whether or not Nrf2 is responsible for HO-1 induction in seawater-induced ALI is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors which can induce HO-1 expression, Nrf2 has a key role in regulating cellular antioxidant stress and eliminating reactive oxygen species (ROS) [11]. Recently research found that Nrf2 prevents oxidative stress-induced pulmonary diseases [12,13]. However, whether or not Nrf2 is responsible for HO-1 induction in seawater-induced ALI is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Even with the increased recognition of ARDS, its identification still depends on various clinical and imaging signs [4], and the treatment of ARDS relies on supportive therapy [5]. Lipopolysaccharide (LPS), a part of the outer membrane of gram-negative bacteria, is one of the most important causes of ALI [6,7]. Intratracheal administration of LPS in mice leads to edema caused by alveolar inflammation, which simulates ARDS in experimental animal model, visually [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors that induce HO-1 expression, Nrf2 has a key role in regulating cellular antioxidant stress and eliminating reactive oxygen species (ROS) [11]. Recent research found that Nrf2 prevents oxidative stressinduced pulmonary diseases [12,13]. However, whether or not Nrf2 is responsible for HO-1 induction in seawater-induced ALI is still unknown.…”
Section: Introductionmentioning
confidence: 99%